Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Certainly! Let's go through the steps to find \(\sec \theta + \tan \theta\) given that \(\sin \theta = \frac{a}{b}\). Here, we'll consider \(a\) and \(b\) as example values to demonstrate the process.
1. Given:
[tex]\[ \sin \theta = \frac{a}{b} \][/tex]
2. Determine \(\cos \theta\):
Using the Pythagorean identity:
[tex]\[ \sin^2 \theta + \cos^2 \theta = 1 \][/tex]
Substituting \(\sin \theta\):
[tex]\[ \left(\frac{a}{b}\right)^2 + \cos^2 \theta = 1 \][/tex]
Simplify:
[tex]\[ \frac{a^2}{b^2} + \cos^2 \theta = 1 \][/tex]
Rearrange to solve for \(\cos^2 \theta\):
[tex]\[ \cos^2 \theta = 1 - \frac{a^2}{b^2} \][/tex]
Simplify further:
[tex]\[ \cos^2 \theta = \frac{b^2 - a^2}{b^2} \][/tex]
Taking the square root of both sides:
[tex]\[ \cos \theta = \sqrt{\frac{b^2 - a^2}{b^2}} = \frac{\sqrt{b^2 - a^2}}{b} \][/tex]
3. Calculate \(\sec \theta\):
Recall that \(\sec \theta = \frac{1}{\cos \theta}\):
[tex]\[ \sec \theta = \frac{1}{\frac{\sqrt{b^2 - a^2}}{b}} = \frac{b}{\sqrt{b^2 - a^2}} \][/tex]
4. Calculate \(\tan \theta\):
Recall that \(\tan \theta = \frac{\sin \theta}{\cos \theta}\):
[tex]\[ \tan \theta = \frac{\frac{a}{b}}{\frac{\sqrt{b^2 - a^2}}{b}} = \frac{a}{\sqrt{b^2 - a^2}} \][/tex]
5. Add \(\sec \theta\) and \(\tan \theta\):
Combine the expressions for \(\sec \theta\) and \(\tan \theta\):
[tex]\[ \sec \theta + \tan \theta = \frac{b}{\sqrt{b^2 - a^2}} + \frac{a}{\sqrt{b^2 - a^2}} \][/tex]
Since the denominators are the same, you can combine the fractions:
[tex]\[ \sec \theta + \tan \theta = \frac{b + a}{\sqrt{b^2 - a^2}} \][/tex]
Therefore, given \(\sin \theta = \frac{a}{b}\), the expression for \(\sec \theta + \tan \theta\) in terms of \(a\) and \(b\) is:
[tex]\[ \sec \theta + \tan \theta = \frac{b + a}{\sqrt{b^2 - a^2}} \][/tex]
1. Given:
[tex]\[ \sin \theta = \frac{a}{b} \][/tex]
2. Determine \(\cos \theta\):
Using the Pythagorean identity:
[tex]\[ \sin^2 \theta + \cos^2 \theta = 1 \][/tex]
Substituting \(\sin \theta\):
[tex]\[ \left(\frac{a}{b}\right)^2 + \cos^2 \theta = 1 \][/tex]
Simplify:
[tex]\[ \frac{a^2}{b^2} + \cos^2 \theta = 1 \][/tex]
Rearrange to solve for \(\cos^2 \theta\):
[tex]\[ \cos^2 \theta = 1 - \frac{a^2}{b^2} \][/tex]
Simplify further:
[tex]\[ \cos^2 \theta = \frac{b^2 - a^2}{b^2} \][/tex]
Taking the square root of both sides:
[tex]\[ \cos \theta = \sqrt{\frac{b^2 - a^2}{b^2}} = \frac{\sqrt{b^2 - a^2}}{b} \][/tex]
3. Calculate \(\sec \theta\):
Recall that \(\sec \theta = \frac{1}{\cos \theta}\):
[tex]\[ \sec \theta = \frac{1}{\frac{\sqrt{b^2 - a^2}}{b}} = \frac{b}{\sqrt{b^2 - a^2}} \][/tex]
4. Calculate \(\tan \theta\):
Recall that \(\tan \theta = \frac{\sin \theta}{\cos \theta}\):
[tex]\[ \tan \theta = \frac{\frac{a}{b}}{\frac{\sqrt{b^2 - a^2}}{b}} = \frac{a}{\sqrt{b^2 - a^2}} \][/tex]
5. Add \(\sec \theta\) and \(\tan \theta\):
Combine the expressions for \(\sec \theta\) and \(\tan \theta\):
[tex]\[ \sec \theta + \tan \theta = \frac{b}{\sqrt{b^2 - a^2}} + \frac{a}{\sqrt{b^2 - a^2}} \][/tex]
Since the denominators are the same, you can combine the fractions:
[tex]\[ \sec \theta + \tan \theta = \frac{b + a}{\sqrt{b^2 - a^2}} \][/tex]
Therefore, given \(\sin \theta = \frac{a}{b}\), the expression for \(\sec \theta + \tan \theta\) in terms of \(a\) and \(b\) is:
[tex]\[ \sec \theta + \tan \theta = \frac{b + a}{\sqrt{b^2 - a^2}} \][/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.